2006
DOI: 10.1128/jb.188.8.3110-3115.2006
|View full text |Cite
|
Sign up to set email alerts
|

EspF of Enteropathogenic Escherichia coli Binds Sorting Nexin 9

Abstract: EspF of enteropathogenic Escherichia coli targets mitochondria and subverts a number of cellular functions. EspF consists of six putative Src homology 3 (SH3) domain binding motifs. In this study we identified sorting nexin 9 (SNX9) as a host cell EspF binding partner protein, which binds EspF via its amino-terminal SH3 region. Coimmunoprecipitation and confocal microscopy showed specific EspF-SNX9 interaction and nonmitochondrial protein colocalization in infected epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 27 publications
4
58
0
1
Order By: Relevance
“…Enrichment analysis showed that the target proteins were enriched in five main types of MF: ribosome structure (p = 0.012), GTPase activity (p = 0.013), protein binding (p = 0.030), RNA binding (p = 0.038) and RNA splicing activity (p = 0.048; Table 3). Studies have shown that EspF has the ability to target mitochondria and nucleoli [6,16], and interacts with N-WASP, SNX9 and Abcf2 [8,[17][18], leading to microvilli disappearance, cytoskeleton rearrangement, actin aggregation, mitochondrial dysfunction and apoptosis in intestinal epithelial cells, nucleolysis and other functions [11,39]. EspF with GTPase activity combined with splicing RNA and other functions in the host cell remains unknown research territory, deserving of further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enrichment analysis showed that the target proteins were enriched in five main types of MF: ribosome structure (p = 0.012), GTPase activity (p = 0.013), protein binding (p = 0.030), RNA binding (p = 0.038) and RNA splicing activity (p = 0.048; Table 3). Studies have shown that EspF has the ability to target mitochondria and nucleoli [6,16], and interacts with N-WASP, SNX9 and Abcf2 [8,[17][18], leading to microvilli disappearance, cytoskeleton rearrangement, actin aggregation, mitochondrial dysfunction and apoptosis in intestinal epithelial cells, nucleolysis and other functions [11,39]. EspF with GTPase activity combined with splicing RNA and other functions in the host cell remains unknown research territory, deserving of further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The number of reads is proportional to the intensity of the interaction between proteins. As is known, SNX9 has been demonstrated to interact with EspF [17]; we have indeed screened it, but it was not obvious in the cloud because the number of reads was not high. We suspect that the expression of this protein may be low, although an interaction may not be apparent because the number of reads is not high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNX9 has been implicated in many cellular functions, having been shown, for example, to bind Ack2 so as to modulate epidermal growth factor degradation and potentially Drosophila axonal guidance (31,32) and to interact with the Escherichia coli EpsF protein to potentially regulate EpsF pathophysiologic effects (41). SNX9 also mediates transferrin endocytosis and binds to and stimulates GTPase activity of dynamins 1 and 2, promoting dynamin-mediated formation and maturation of clathrin-coated pits (30,33).…”
Section: Discussionmentioning
confidence: 99%
“…Like EspF U , EspF consists of an N-terminal translocation domain and several 47-residue Cterminal repeats, each of which contains an N-WASP binding segment and a proline-rich sequence that is recognized by an SH3 domain-containing protein that binds and deforms membranes. In the case of EspF, the SH3-containing protein is SNX9 (29,30), which contains a BAR domain and participates in membrane remodeling during endocytosis (31). Although EspF U can complement some functions of EspF (32), EspF plays no apparent role in pedestal formation (15), presumably because its proline-rich sequences target a different SH3 domain.…”
Section: Discussionmentioning
confidence: 99%